Institutional affiliations and socialization: Doctoral Thesis in History of Education in Spain (1990-2010) - Sanchidrián-Blanco, María del Carmen (My University, 2018)
This paper is divided into two parts: a) After the previous studies of the temporal and spatial delimitations and the object of study, we have moved into the institutional factors, such as advisors and institutions. The focus of this study is the professional link of both advisors and institutions to the history of Education. This issue is particularly relevant in the Spanish case where most of the Theses have been done mainly in two different fields (Faculties of Education or Faculties of Arts) that not only have a different “culture” but also a different background. b) We are exploring if writing a doctoral thesis in History of Education can be seen as a way of socialization in our field. On the one hand, we have studied if these authors have published (articles, books, conference papers and posters) the results of their Dissertations and where (especially journals and conferences of History, History of Education or others). On the other hand, we want to know if the authors have done further contributions in History of Education (if the authors stay in our field) or in a different one and their presence in some academic networks (Google Scholar, ResearchGate and Dialnet).
Presentación en el SWG MAPPING THE DISCIPLINE HISTORY OF EDUCATION INSTITUTIONAL IMPACT ON HISTORY OF EDUCATION RESEARCH en ISCHE 40
Keywords: Tesis doctorales - Congresos; PhD,; History of Education; Spain; Doctoral Studies